2020
DOI: 10.1080/16583655.2020.1746600
|View full text |Cite
|
Sign up to set email alerts
|

Extracting the optical parameters of thermally evaporated Se film by modelling of transmittance spectra: Effect of heat treatment

Abstract: Thin Se films with an appropriate thickness were deposited by the thermal evaporation technique on glass substrates that are grasped at a temperature of ∼ 300 K. The as-deposited amorphous Se thin films were heat-treated in N 2 ambient for 1 h at different annealing temperatures that ranged from 323 to 363 K. The transmittance spectra of green and annealed Se films have been measured at vertical incidence angle along the wavelength range of 300-2500 nm. For the first time, the dielectric function (OJL2) model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…It can also be observed that the transmittance data of samples shown exhibit interference effects. These interference fringes can be used as an indicator for the thickness of the films [31], where it can be observed that the films have different thickness due to the different configurations and oxygen percentages. As previously mentioned, all coatings have the same deposition time of 72 h, where the thicknesses varies between 140 -270 nm, dependent on the coating configurations.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It can also be observed that the transmittance data of samples shown exhibit interference effects. These interference fringes can be used as an indicator for the thickness of the films [31], where it can be observed that the films have different thickness due to the different configurations and oxygen percentages. As previously mentioned, all coatings have the same deposition time of 72 h, where the thicknesses varies between 140 -270 nm, dependent on the coating configurations.…”
Section: Resultsmentioning
confidence: 99%
“…OJL model is used to describe the interband transition in the amorphous semiconductors [30,31]. This model assumes the parabolic shape valance and conduction band of the DOS, with tail states exponentially decaying into the bandgap [29][30][31].…”
Section: Optical Characterizationmentioning
confidence: 99%
See 3 more Smart Citations